Diseño de un sistema para la producción de planchas biodegradables a base de la tusa de maíz - Rodríguez Bravo, Daniel Oswaldo (2022)
This research project proposes a constructive solution for insulating materials from residual agricultural biomass particles (corn cob) with a binder of synthetic origin (Blancola or Carpincol MR-60). The design of the constructive model proposes several dosages in relation to the corncob weight (50/50 and 70/30) and the particle size (coarse and medium) with the purpose of generating added value to this type of waste and proposing an action environmental mitigation to reduce contamination by agricultural residues. The thermal characterization of the residual biomass is carried out by means of the manufacture of agglomerated particle boards to later determine the influence of the design parameters of the board through the analysis of variance, Tukey method, Brinell hardness test. The test methods for the board were carried out according to the INEN 3110-2016 Standard in terms of biodegradable products and their performance was later determined to guarantee their application. Keywords: Agglomerate, corncob, residual biomass, biodegradable.